Grantchester. The complete fifth season [videorecording (DVD)] - Anderson, Gordon (Television director); Ebohon-Green, Christiana; Evans, Rob; Green, Robson; Peake-Jones, Tessa; Weaver, Al, 1981-; Ainsworth, Kacey (PBS, 2020)
It's 1957, and it's as if the world of Grantchester has returned to an idyllic state, a metaphorical Garden of Eden. Will believes that everyone can get close to their own Eden through good works and a proactive attitude. But as Geordie knows, every Eden has its snakes. Will's faith will be tested as he and Geordie are reminded that there's darkness lurking in their corner of Cambridgeshire.